Acute toxicity studies of a novel excipient arabinoxylan isolated from Ispaghula (Plantago ovata) husk. (July 2015) - Erum, Alia; Bashir, Sajid; Saghir, Shazia; Tulain, Ume Ruqia; Saleem, Uzma; Nasir, Muhammad; Kanwal, Farina; Hayat malik, Muhammad Nasir
Abstract Purpose: The arabinoxylan from Ispaghula (Plantago ovata) husk has been proven scientifically as potential excipient. However, toxicity study of the arabinoxylan is still lacking. The present study was done to investigate the acute toxicity of arabinoxylan in two animal species. Methods: The mice were exposed to (1 g/kg, 5 g/kg, 10 g/kg) and rabbits (2.5 g/kg, 5 g/kg) of arabinoxylan orally and observed for a period of 14 days. On day 15 hematology, serum biochemistry and necropsy was performed in mice relative organ weight calculated and histological examination was carried out. Primary dermal and eye irritation tests were carried out. Cardiac effects of isolated arabinoxylan were studied on frog heart. Results: The acute administration of the arabinoxylan did not produce mortality or significant changes in, water and food consumption however body weights of mice and rabbits decreased initially with a gradual increase till day 14. Internal organs relative weights were found to be normal. Hematological biochemical and histopathological examination did not show any significant (p < 0.05) change. Primary dermal and eye irritation was not observed in treated rabbits. No change in heart rate and vascular contraction was observed in frog heart. Conclusion: This study has shown that acute administration of arabinoxylan may be safe.